High-resolution TDPAC measurement in K₂ZrF₆ - Martínez, Jorge Alberto (1981)
A time resolution of 2τ=0.75 ns, achieved with a conventional TDPAC setup with FCs detectors, allowed a determination of the very high electric field gradient at Hf impurity sites in K2ZrF6. Simple theoretical calculations seem to indicate that nearest neighbours are responsible for the interaction observed.